Grain Dust Explosions Up in 1994 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
There were 15 grain dust explosions reported for the U.S. in 1994 according to Robert W. Schoeff, Professor Emeritus and Consultant, Kansas State University and Ralph Regan, Safety Director, USDA-FGIS. This compares to 13 in 1993 and a ten-year average of 15 explosions.
Keywords: Grain dust; Dust explosions